2021
DOI: 10.1002/ncp.10812
|View full text |Cite
|
Sign up to set email alerts
|

Monitor gastrointestinal tolerance in children who have switched to an “enteral formula with food‐derived ingredients”: A national, multicenter retrospective chart review (RICIMIX study)

Abstract: Background Enteral tube feeding intolerances, such as diarrhea, are commonly reported in children. In the pediatric population, interest is growing in the use of blended diets for the management of enteral feeding intolerances. Fiber within a blended diet stimulates the growth of beneficial gut bacteria, which in turn produce short‐chain fatty acids, which are utilized as energy substrates for enterocytes. Enteral formula manufacturers have responded to this trend towards “real‐food” blended diets and develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…7,16 A recent, multicenter, retrospective study of 43 children who were medically unwell found improvements in GI symptoms when participants switched to an enteral formula based on realfood ingredients. 9 Similarly, a prospective, observational study of 21 children with neurological impairments who switched to a 1.0 kcal/ml real-food formula reported that calorie and protein goals were achieved without intolerance or serious adverse events. 15 Another study examined a lowcalorie real-food formula in 16 hypometabolic pediatric patients with neurological impairments or neuromuscular disorders, who would traditionally receive standard enteral formulas manipulated with modular protein, vitamins, minerals, and water.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7,16 A recent, multicenter, retrospective study of 43 children who were medically unwell found improvements in GI symptoms when participants switched to an enteral formula based on realfood ingredients. 9 Similarly, a prospective, observational study of 21 children with neurological impairments who switched to a 1.0 kcal/ml real-food formula reported that calorie and protein goals were achieved without intolerance or serious adverse events. 15 Another study examined a lowcalorie real-food formula in 16 hypometabolic pediatric patients with neurological impairments or neuromuscular disorders, who would traditionally receive standard enteral formulas manipulated with modular protein, vitamins, minerals, and water.…”
Section: Discussionmentioning
confidence: 99%
“…3,18 Frequently, clinicians use the presence of upper and lower GI symptoms to help assess formula tolerance. 9,17 In a recent Canadian study, GI-related complications of HEN (including nausea and vomiting, abdominal pain, constipation, and diarrhea) occurred in…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent retrospective, multi-centre study also explored the benefits of Compleat ® paediatric (O'Connor et al, 2021). The authors collected data from 43 tube-fed children.…”
Section: Where Are We Now?mentioning
confidence: 99%